Reduced deoxyribonuclease enzyme activity in response to high postinjury mitochondrial DNA concentration provides a therapeutic target for Systemic Inflammatory Response Syndrome. Issue 2 (August 2018) - McIlroy, Daniel J.; Minahan, Kyra; Keely, Simon; Lott, Natalie; Hansbro, Philip; Smith, Doug W.; Balogh, Zsolt J.
Abstract : BACKGROUND: Cell-free mitochondrial DNA (mtDNA) is proinflammatory and has been detected in high concentrations in trauma patients' plasma. Deoxyribonuclease (DNAse) is the free plasma enzyme responsible for the digestion of extracellular DNA. The relationship between mtDNA and DNAse after major trauma is unknown. We hypothesized that DNAse activity would be elevated after injury and trauma surgery and would be associated with high concentrations of extracellular DNA. METHODS: Two-year prospective study was performed on 103 consecutive trauma patients (male, 81%; age, 38 years [interquartile range, 30–59 years]; injury severity score, 18 [interquartile range, 12–26 years]) who underwent standardized major orthopedic trauma surgical interventions. Blood was collected at five perioperative time points (preoperative, postoperative, 7 hours, 24 hours, and 3 days postoperatively). Healthy control subjects (n = 20) were also sampled. Cell-free mtDNA and nuclear DNA (nDNA) were measured using quantitative polymerase chain reaction. Deoxyribonuclease was also assayed in the same plasma samples. RESULTS: Increased levels of mtDNA (from preoperative 163 ± 86 ng/mL to 3 days 282 ± 201 ng/mL, p < 0.0001) and nDNA (from preoperative 28 ± 20 ng/mL to 3 days 37 ± 27 ng/mL, p < 0.05) were present in trauma patients at all perioperative time points compared with healthy controls (mtDNA: 4 ± 2 ng/mL; nDNA: 10 ± 5 ng/mL). Deoxyribonuclease activity was lower in the trauma cohort (from preoperative 0.06 ± 0.04U/mL to 3 days 0.08 ± 0.04U/mL, p < 0.0001) compared with healthy controls (DNAse: 0.17 ± 0.03U/mL). There was no correlation between DNAse and perioperative DNA concentrations. Elevated mtDNA (but not nDNA) correlated with the development of systemic inflammatory response syndrome (SIRS) ( p = 0.026) but not multiple organ failure. CONCLUSIONS: The significant perioperative elevation in plasma-free mtDNA concentration is associated with the development of SIRS. The fact that increased cell-free DNA concentrations present with significantly lower than healthy control DNAse activity suggests a potential therapeutic opportunity with DNAse administration to modulate postinjury severe SIRS. LEVEL OF EVIDENCE: Prognostic/Epidemiological, level II.